Economic Diversification Potential in the Rentier States Towards for a Sustainable Development: A Theoretical Model - Abdullah Kaya (44754) (2019)
This paper develops a theoretical model to analyze whether a rentier state can diversify its economy away from the rent revenue and hence sustain the economic development and preserve the status-quo. Considering the decarbonization process of the global economy and rapidly fall in economic value of hydrocarbons in the face of the supply glut, rentier states depending on oil and gas revenues urgently need to diversify their economies to avoid social backlash and political upheaval. There are three intertwining factors that determine an effective economic diversification away from the rent revenue: The profitability of non-rentier sectors, the size of the domestic economy to induce a “Big Push” for industrialization to non-rentier sectors, and the level of economic inclusivity. For an optimal level of economic diversification in a rentier state: (1) Non-rentier sectors should be attractive to private agents without the entry barriers; (2) domestic economy should be large enough to induce investment into non-rentier sectors; (3) the ruler(s) should have sufficient tolerance (inclusivity) for private agents investing into non-rentier sectors. Our findings indicate that a rentier state can achieve an optimal level of economic diversification provided that the conditions above are met even without any political change. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su11030911